Keterampilan Guru Dalam Merancang LKS Di SDN 060909 Medan Denai - Safran Safran; Aulia Rahmadani; Tiara Paramita Br Purba (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This article aims to find out about teacher skills in designing a student worksheet (LKS) at SDN 060909 Medan Denai. The method used by researchers is a qualitative research method using interview and observation data collection techniques for one research subject, namely the class 1 teacher at SDN 060909 Medan Denai. Using interview and observation data collection techniques. The research results show that the teacher's skills in designing a student worksheet are good. It can be seen from the teacher's ability to utilize technology such as using the Canva application to design a worksheet and also using the LKS web on Google as well as the design results which are quite interesting accompanied by animated images that are appropriate for the age of elementary school students. The LKS designed by research subjects is very simple, therefore there are several important components that are not included in the LKS designed, such as the competencies to be achieved and supporting information.